Powder neutron diffraction study of phase transitions in and a phase diagram of (1-x) [Pb (Mg1 3 Nb2 3) O3] -xPbTi O3 - Singh A.K.; Pandey D.; Zaharko O. (My University, 2025)
Dielectric, piezoelectric resonance frequency, and powder neutron diffraction studies as a function of temperature have been performed on several compositions of (1-x) [Pb (Mg1 3 Nb2 3) O3] -xPbTi O3 (PMN-xPT) ceramics in and outside the morphotropic phase boundary (MPB) region to investigate the phase transitions and phase stabilities in this mixed system. Anomalies in the temperature dependence of piezoelectric resonance frequency and dielectric constant are correlated with structural changes using Rietveld analysis of powder neutron diffraction data. The frequency dependent dielectric studies reveal relaxor ferroelectric behavior for x<0.35 and a normal ferroelectric behavior for x≥0.35. The dielectric peak temperature and the Vogel-Fulcher freezing temperature are found to increase linearly with "x" while their difference, after decreasing linearly with x, vanishes at x=0.35 suggesting a crossover form relaxor ferroelectric to normal ferroelectric behavior at this composition. A phase diagram of the PMN-xPT system showing the stability fields of ergodic relaxor, monoclinic MB, monoclinic MC, tetragonal and cubic phases is presented. Our results suggest the presence of a succession of three phase transitions, not reported earlier, corresponding to structural changes from the monoclinic MB to the monoclinic MC to the tetragonal to the cubic phases for 0.27≤x≤0.30 on heating above room temperature. In addition, our studies confirm the earlier findings on transitions from the monoclinic MC to the tetragonal to the cubic phases for 0.31≤x≤0.34 on heating above room temperature and tetragonal to monoclinic MC phase on cooling below room temperature for x=0.36. All these transitions are found to be accompanied with anomalies either in the temperature dependence of dielectric constant or the piezoelectric resonance frequency or both. Rietveld analyses of the powder neutron diffraction data at various temperatures on a pseudorhombohedral composition with x=0.25 suggest that the short range MB type monoclinic order present at room temperature grows to long range monoclinic order on lowering the temperature. The temperature variations of the unit cell parameters and atomic shifts are also presented to throw light on the nature of the various phase transitions in this mixed system. © 2006 The American Physical Society.